2005
DOI: 10.1111/j.1467-8624.2005.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influences in Different Aspects of Language Development: The Etiology of Language Skills in 4.5‐Year‐Old Twins

Abstract: The genetic and environmental etiologies of diverse aspects of language ability and disability, including articulation, phonology, grammar, vocabulary, and verbal memory, were investigated in a UK sample of 787 pairs of 4½ year-old same-sex and opposite-sex twins. Moderate genetic influence was found for all aspects of language in the normal range. A similar pattern was found at the low end of the distribution with the exception of two receptive measures. Environmental influence was mainly due to nonshared fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
98
3
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(114 citation statements)
references
References 58 publications
8
98
3
5
Order By: Relevance
“…These results are consistent with a large body of behavioural genetic findings, suggesting that heritability of pre-school early literacy indicators is on average lower (e.g. Kovas et al, 2005) than substantial heritability of literacy found throughout formal school education (e.g. Harlaar et al, 2005;Byrne et al, 2006;Kovas et al, 2013).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…These results are consistent with a large body of behavioural genetic findings, suggesting that heritability of pre-school early literacy indicators is on average lower (e.g. Kovas et al, 2005) than substantial heritability of literacy found throughout formal school education (e.g. Harlaar et al, 2005;Byrne et al, 2006;Kovas et al, 2013).…”
supporting
confidence: 88%
“…For example, the pattern of results that emerged from cross-cultural longitudinal research on literacy is consistent with the hypothesis of greater equality leading to greater heritability (e.g. Kovas et al, 2005;Samuelsson et al, 2008;Hayiou-Thomas, 2008). The research demonstrated that heritability of reading skills varies as a function of students' age and educational set-up, including the extent to which the formal education system is able to buffer the effects of socioeconomic inequality.…”
Section: Age Cohorts Within and Across Countriessupporting
confidence: 62%
“…Although cognitive and language data were obtained in TEDS at 2–4 years (e.g., Colledge et al, 2002; Dale et al, 1998; Dale, Dionne, Eley, & Plomin, 2000; Dionne, Dale, Boivin, & Plomin, 2003; Hayiou-Thomas et al, 2006; Kovas et al, 2005; Price, Dale, & Plomin, 2004; Spinath, Ronald, Harlaar, Price, & Plomin, 2003; Spinath, Harlaar, Ronald, & Plomin, 2004; Viding et al, 2003; Viding et al, 2004), the focus of this monograph is on learning abilities assessed at 7, 9, and 10 years. These ages correspond to the early school years during which important changes in academic content occur, reflected in the U.K. National Curriculum (NC) by a second key stage (see Appendices A–C).…”
Section: Methodsmentioning
confidence: 99%
“…Reported estimates of group heritability for language difficulty have ranged from .25 to 1.00 (Stromswold, 2001; see also , but most studies report moderate genetic effects that are relatively comparable to the estimate of .54 obtained here. For example, Bishop (2002) reported group heritability estimates of .65 and .80 for low scores in word finding and recalling sentences, whereas Kovas et al (2005) reported estimates of .51 and .69 for low scores on expressive semantic measures. Of interest, Kovas et al found no significant genetic effect on a measure of expressive grammar.…”
Section: Genetic Effectsmentioning
confidence: 99%
“…Group heritability estimates for individual measures were .65 and .80 for expressive language, .48 and 1.23 for receptive language, and .97 for articulation (see also Bishop, North, & Donlan, 1995). A study by Kovas et al (2005) examined the extent of genetic and environmental effects on different aspects of speech-language development and disability using 787 pairs of 4-year-old twins from the Twins Early Development Study. Probands were identified with scores that fell more than one standard deviation below the sample's mean.…”
mentioning
confidence: 99%